3D Interconnected Porous Graphitic Carbon@MoS2 Anchored on Carbonized Cotton Cloth as an Anode for Enhanced Lithium Storage Performance. (10th October 2019) - Sun, Dongfei; Miao, Xuan; He, Yijuan; Wang, Li; Zhou, Xiaozhong; Ma, Guofu; Lei, Ziqiang
Abstract: Developing advanced electrode materials with hierarchical porous structure is one of the promising strategies to achieve superior properties in lithium-ion batteries (LIBs). Herein, this study reports the design and fabrication of MoS2 nanosheets @ 3D interconnected porous graphitic carbon anchored on carbonized cotton cloth (CC/PGC@MoS2 ) as an anode for LIBs. The uniform interconnected porous PGC@MoS2 is not only grown on the surface of carbon fibers of CC, but also filled in the spaces among carbon fibers to achieve a dense and interconnected conductive network. The intermediate graphitic carbon network in CC/PGC@MoS2 nanostructure can greatly enhance the electronic conductivity, provide short ion transport paths and create abundant active sites. Benefiting from its unique structure, the CC/PGC@MoS2 electrode delivers a high reversible capacity (reversible capacity of 1095.1 mA h g −1 at 0.1 A g −1 ), excellent rate capability, and remarkable cycling stability (reversible capacity of 816 mA h g −1 at 1.0 A g −1 after 400 cycles), making it promise as an electrode material for LIBs. This study provides a new strategy for designing carbon-based materials with superior electrochemical properties.